Reinventing the wheel : a Buddhist response to the information age - Hershock, Peter D. (SUNY series in philosophy and biology., 1999)
"By uniquely using Buddhist teachings, Reinventing the Wheel assesses the personal and communal costs of our global economic and technological commitments. Hershock urges reinvention of the technological "wheel," and, at the same time acknowledges the need for new forms of practice suited to our rapidly evolving social, political, and economic circumstances. His persuasive presentation urges the skillful spinning of a new "wheel of the dharma.""--Jacket